Cooperative Learning: Developments in Research - Gillies, Robyn M. (International Journal of Educational Psychology, 2014)
Cooperative learning is widely recognized as a pedagogical practice that promotes socialization and learning among students from kindergarten through to college level and across different subject areas. Cooperative learning involves students working together to achieve common goals or complete group tasks. Interest in cooperative learning has grown rapidly over the last three decades as research has been published that clearly demonstrates how it can be used to promote achievements in reading and writing, conceptual development in science, problem-solving in mathematics, and higher level thinking and reasoning. It has also been shown to promote inter-personal relationships with students with diverse learning and adjustments needs and with those from culturally and ethnically different backgrounds. In fact, Johnson and Johnson (2000)argue there is no other pedagogical practice that achieves such outcomes. The purpose of this paper is to review the research on cooperative learning and to examine the factors that contribute to its success. In particular, the review focuses on the key elements that underpin successful cooperative learning, including group structure, composition and task, and the key role teachers’ play in developing students’ thinking and learning. The intention is to provide insights on how teachers can effectively utilize this pedagogical approach to teaching and learning in their classrooms.